2008
DOI: 10.1097/iae.0b013e318162b008
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Hypotony After 25-Gauge Sutureless Vitrectomy With Straight Incisions

Abstract: Twenty-five-gauge sutureless vitrectomy with straight incisions resulted in a hypotony rate of 26.12% at 2 hours that decreased to 17.11% on day 1 and to 8.10% at week 1 but did not increase the incidence of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 19 publications
1
32
1
8
Order By: Relevance
“…27,28 This is important because postoperative hypotony is not uncommon after sutureless vitrectomy, which might allow bacterial entry into the vitreous through the sclerotomy sites. This could then lead to postoperative endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 This is important because postoperative hypotony is not uncommon after sutureless vitrectomy, which might allow bacterial entry into the vitreous through the sclerotomy sites. This could then lead to postoperative endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…20 ). Similarly, Acar et al observed an incidence of hypotony under 8 mmHg in 17.1% of the eyes when straight sclerotomies were performed and intraocular tamponade was not used 21 . Bourgault, however, did not prove that oblique sclerotomies decreased the incidence of postoperative hypotony compared to straight sclerotomies both in eyes with gas tamponade or without tamponade (9.9% vs. 9.2%; P=0.85) (ref.…”
Section: Discussionmentioning
confidence: 84%
“…In previous reports, the hypotony incidence after 25-gauge vitrectomy has been reported to be 0-30% at the first postoperative day 1 [4,6,7]. Early hypotony has also been reported to occur as early as postoperative hour 2 without any clinically prominent leakage by slitlamp examination [7].…”
Section: Discussionmentioning
confidence: 96%
“…The incidence of hypotony after 25-gauge vitrectomy has been described in several prospective and retrospective case series and was reported to be anywhere between 0% to 20% on post-operative day one [4,[6][7][8][9][10][11][12][13]. It has been noted to occur even in cases of 25-gauge vitrectomy that had sutures placed at the conclusion of surgery to close sclerotomies that appeared to persistently leak after cannula removal [7].…”
Section: Introductionmentioning
confidence: 99%